Emergency Department Visits After Elective Spine Surgery. Issue 2 (28th September 2018) - Hills, Jeffrey M; Khan, Inamullah; Sivaganesan, Ahilan; Weisenthal, Benjamin; Daryoush, Joshua; Butler, Marjorie; Bydon, Mohamad; Archer, Kristin R; Asher, Anthony; Devin, Clinton J
Abstract: BACKGROUND: Emergency department (ED) overuse is a costly and often neglected source of postdischarge resource utilization after spine surgery. Failing to investigate drivers of ED visits represents a missed opportunity to improve the value of care in spine patients. OBJECTIVE: To identify the prevalence, drivers, and timing of ED visits following elective spine surgery. METHODS: Patients undergoing elective spine surgery for degenerative disease at a major medical center were enrolled in a prospective longitudinal registry. Patient and surgery characteristics, and patient-reported outcomes were recorded at baseline and 3 mo after surgery, along with self-reported 90-d ED visits. A multivariable regression model was used to identify independent factors associated with 90-d ED visits. For a sample of patients presenting to our institution's ED, charts were reviewed to identify the reason and time to ED postdischarge. RESULTS: Of 2762 patients, we found a 90-d ED visit rate of 9.4%. One-third of patients presented to our institution's ED and of these, 70% presented due to pain or medical concerns at 9 and 7 d postdischarge, respectively, with 60% presenting outside normal clinic hours. Independent risk factors for 90-d ED visits included younger age, preoperative opioid use, chronic obstructive pulmonary disorder, and more vertebral levels involved. CONCLUSION: Nearly 10% of elective spine patients had 90-d ED visits not requiring readmission. Pain and medical concerns accounted for 70% of visits at our center, occurring within 10 d of discharge. This study provides the clinical details and a timeline necessary to guide individualized interventions to prevent unnecessary, costly ED visits after spine surgery.